Confirmation of a Causal Taar1 Allelic Variant in Addiction-Relevant Methamphetamine Behaviors - Phillips, Tamara J.; Roy, Tyler; Aldrich, Sara J.; Baba, Harue; Erk, Jason; Mootz, John R. K.; Reed, Cheryl; Chesler, Elissa J. (Frontiers in Psychiatry, 2021)
Sensitivity to rewarding and reinforcing drug effects has a critical role in initial use, but the role of initial aversive drug effects has received less attention. Methamphetamine effects on dopamine re-uptake and efflux are associated with its addiction potential. However, methamphetamine also serves as a substrate for the trace amine-associated receptor 1 (TAAR1). Growing evidence in animal models indicates that increasing TAAR1 function reduces drug self-administration and intake. We previously determined that a non-synonymous single nucleotide polymorphism (SNP) in Taar1 predicts a conformational change in the receptor that has functional consequences. A Taar1m1J mutant allele existing in DBA/2J mice expresses a non-functional receptor. In comparison to mice that possess one or more copies of the reference Taar1 allele (Taar1+/+ or Taar1+/m1J), mice with the Taar1m1J/m1J genotype readily consume methamphetamine, express low sensitivity to aversive effects of methamphetamine, and lack sensitivity to acute methamphetamine-induced hypothermia. We used three sets of knock-in and control mice in which one Taar1 allele was exchanged with the alternative allele to determine if other methamphetamine-related traits and an opioid trait are impacted by the same Taar1 SNP proven to affect MA consumption and hypothermia. First, we measured sensitivity to conditioned rewarding and aversive effects of methamphetamine to determine if an impact of the Taar1 SNP on these traits could be proven. Next, we used multiple genetic backgrounds to study the consistency of Taar1 allelic effects on methamphetamine intake and hypothermia. Finally, we studied morphine-induced hypothermia to confirm prior data suggesting that a gene in linkage disequilibrium with Taar1, rather than Taar1, accounts for prior observed differences in sensitivity. We found that a single SNP exchange reduced sensitivity to methamphetamine conditioned reward and increased sensitivity to conditioned aversion. Profound differences in methamphetamine intake and hypothermia consistently corresponded with genotype at the SNP location, with only slight variation in magnitude across genetic backgrounds. Morphine-induced hypothermia was not dependent on Taar1 genotype. Thus, Taar1 genotype and TAAR1 function impact multiple methamphetamine-related effects that likely predict the potential for methamphetamine use. These data support further investigation of their potential roles in risk for methamphetamine addiction and therapeutic development.